Lexico-Semantic Properties of Literature Positive Assessment Units (Eurasian Research Bulletin, 2022)
The article provides an analysis of words that express a positive assessment. Words that express a positive assessment are illustrated with examples and their lexical and semantic aspects are explained in detail. Theoretical opinions of scientists are quoted and commented on.